Morphosemantic Changes in the Arabic Language in the Social Media Era: A Study of Neologisms and Their Impact on Youth Communication/ التغيرات المورفوسيمانتية في اللغة العربية في عصر وسائل التواصل الاجتماعي: دراسة حول النيو لوغيزم وتأثيرها على تواصل الشباب - Ibnu Fitrianto; Riza Hamid (IJAS: International Journal of Arabic Studies, 2024)
This study examines the morphosemantic changes in the Arabic language in the era of social media, focusing on a study of neologisms and their impact on youth communication. The research concentrates on how new terms emerge through platforms such as Facebook, Twitter, and Instagram, and how these terms affect the development of the Arabic language. A qualitative approach was used, relying on descriptive analysis of data collected from observations, interviews, and documents related to the use of neologisms. The results show that neologisms have led to notable changes in word structure and meanings, with new words formed through word combinations, abbreviations, and adaptations from other languages. The study also revealed that these changes have significantly impacted how youth communicate, leading to the use of informal and easily understandable language in digital interactions. However, the increasing reliance on new terms may lead to a decline in the use of classical Arabic. The study recommends finding a balance between linguistic innovations and preserving linguistic heritage to ensure the continuity of the Arabic language in the future